Infertility treatments and risk of breast benign diseases: a case‒control study - Ashraf Moini; Sadaf Alipour; Zahra Zandi; Arezoo Maleki-Hajiagha; Ladan kashani; Fatemeh Shakki katouli; Maryam Farid Mojtahedi; Leila Bayani; Mahboubeh Abedi (BMC, 2024)
Abstract Background Theoretically, endocrine fluctuations occurring during infertility treatments, including ovulation induction (OI) and assisted reproductive techniques (ART), could be associated with an increased risk of benign breast diseases (BBDs). To date, no studies have been conducted on this association. Therefore, the present study investigated the association between different types of infertility treatments and BBDs. Methods This case‒control study was conducted in Arash Women's Hospital, Tehran, Iran. The case group included infertile women diagnosed with BBDs without atypia, and the control group included infertile women without breast disease. Breast imaging studies (mammography/ultrasound) were performed for BBD screening, and the diagnosis was confirmed by histopathological examination. Study variables were collected retrospectively from medical records, hospital databases, and questionnaires. Results Finally, 154 infertile women, including 50 cases (BBDs) and 104 controls (no BBDs), were compared. Our data showed that 66% of cases and 61.4% of controls had undergone at least one course of infertility treatment. There was no association between BBD risk and previous infertility treatments (OR = 1.21; 95% CI = 0.59-2.46), ART (OR = 1.14; 95% CI = 0.90-1.44), or OI cycles (OR = 1.13; 95% CI = 0.98-1.32). Stratification by confounding variables did not change these results. Conclusions It seems that there is no association between BBDs in infertile women and the type, duration, or number of prior infertility treatments; however, considering the small sample size of the study, the clinical significance of this finding should not be neglected. Therefore, we consider it essential to carry out more extensive, detailed, and prospective studies to distinguish the association of BBDs with different infertility treatments and medications.